A Qualitative Exploration of Barriers to School Education among Adolescent Girls in Nepal - Gnawali, Keshava Raj (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Educated girls have better sense of responsibility that can be instrumental to establish harmony and justice in the society. The access to education of girls in school education is still indiscriminatory in some countries. This research explored barriers to school education among adolescent girls in Nepal using qualitative research methods. This exploration includes 12 Focus Group Discussions (FGDs), 6 in-depth interviews with out-of-school girls and 6 personal interviews with school teachers/ management committee members of six schools in three districts representing mountain, hill and terai. Barriers in three levels: macro level (socio-economic and Institutional), micro level (Inter-personal and Personal) and governance and management level were identified. The study can be helpful devise intervention mechanism to overcome the barriers to school education of adolescent girls in the countries with identical settings like Nepal. How to cite this article: Gnawali KR. A Qualitative Exploration of Barriers to School Education among Adolescent Girls in Nepal. J Adv Res Jrnl Mass Comm 2019; 6(3): 1-9.